Cross sectional study of MR fistulography in the evaluation of perianal fistulae and its surgical correlation - Sameeha Khan; Shiraz Ahamed Sharief; Muneer Ahmed; Ramesh V. Mankare; Hemanth Shetty; Atik Ahmed; Lubna Kauser (Al Ameen Medical College, 2015)
Aims and objectives: To evaluate the diagnostic accuracy of Magnetic Resonance Fistulography in the assessment of the perianal fistulae. Background: The success of the surgical approach for perianal fistulae treatmentis closely associated with the preoperative assessment. MR imaging plays a key role in describing the fistulae in relation to the anatomy of the perianal region. This has been categorised according to the involvement of the fistulous tract in relation to the sphincters and its extension of the disease into five imaging based grades. This helps in selecting the appropriate surgery in order to reduce the load of recurrences. Materials and methods: Over a period of 6 months, a cross sectional study was conducted among 18 patients who were admitted with the features of perianal fistulae at Al-Ameen Medical College Hospital , Vijayapura. The average age of patients was 44.5 years, ranging from 33 to 72 years, with the number of females 22.2% (n = 4) and males 77.8% (n = 14). The pre-operative MR imaging assessment was studied and correlated with intra operative surgical findings. Results: The accuracy of MR Fistulography was consistent with 17 out of 18 surgical findings, except for one case, which was falsely over diagnosed. Conclusion: To conclude, MR Fistulography is an essential investigation of choice in the evaluation of perianal fistulae. It helps in accurate identification of the type of perianal fistula in relation to the anal sphincters and adjacent anatomical structures. Hence this investigation should be recommended routinely in preoperative work up for precise surgical management of perianal fistulae.